Electrospun silk nanofiber loaded with Ag-doped TiO2 with high-reactive facet as multifunctional air filter - Sompit Wanwong; Weradesh Sangkhun; Pimsumon Jiamboonsri; Teera Butburee (My University, 2023)
Silk nanocomposite, made by electrospun of silk nanofiber loaded with Ag-doped TiO 2 , is used as a multifunctional air filter for PM 2.5 removal, VOC degradation and antimicrobial activity.
Keywords: Electrospinning; Photodegradation; Air filter; Air purifier; Environmentally Friendly; Electrospun Nanofibers in Biomedical Applications